Tolerance synthesis for lost motion requirement of planetary gear train based on a mechanism model. (October 2021) - Zhang, Chu; Dong, Huimin; Wang, Delun; Cheng, Yi
Highlights: Proposed an equivalent mechanism for lost motion behavior of planetary gear train. Developed a tolerance synthesis method based on the mechanism model with errors. Validated the method by testing planetary gear trains with allocated tolerances. Abstract: In this paper, an original equivalent mechanism with parallel linkages is proposed for lost motion behavior analysis and tolerance synthesis of planetary gear train (PGT). The parallel linkages are equivalent in kinematics of PGT to depict the multiple branches of sun-planet-ring gears with a driving link/sun gear and an output platform/carrier, a slider-block with two strokes in the circle curve guide rail of the platform is introduced in each linkage to intuitively express the lag rotation of output platform driven by the parallel linkages under error condition, and the errors are described by the deviations of link lengths. With the mechanism model, the lost motion expression of PGT is explicitly derived and then the tolerance synthesis method is formulated to allocate the optimum tolerances for satisfying the lost motion requirement with the minimum manufacturing cost. The lost motion behavior of PGT was simulated and the tolerances of errors were allocated involving tooth thickness reduction, planet position errors and gear eccentricity errors. The lost motion tests of two PGTs with the allocated tolerances were conducted. The results well agree with the simulations', which validated the effectiveness of the developed tolerance synthesis method by the proposed mechanism model.